2002
DOI: 10.2172/795970
|View full text |Cite
|
Sign up to set email alerts
|

Energy savings for heat-island reduction strategies in Chicago and Houston (including updates for Baton Rouge, Sacramento, and Salt Lake City)

Abstract: In 1997, the U.S. Environmental Protection Agency (EPA) established the "Heat Island Reduction Initiative" to quantify the potential benefits of Heat-Island Reduction (HIR) strategies (i.e., shade trees, reflective roofs, reflective pavements and urban vegetation) to reduce coolingenergy use in buildings, lower the ambient air temperature and improve urban air quality in cities, and reduce CO 2 emissions from power plants. Under this initiative, the Urban Heat Island Pilot Project (UHIPP) was created with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…However, because there is no standard protocol for quantifying these urban heat island-related externalities, comparisons among these three roofing strategies are limited. To date there have been a number of published case studies that compare green roofs to black roofs [9][10][11][12][13] and white roofs to black roofs [14][15][16][17]. However, we could not find a comprehensive comparison of green and white roofs.…”
Section: Sproul Et Al (Version Dated 11/01/2013)mentioning
confidence: 95%
See 1 more Smart Citation
“…However, because there is no standard protocol for quantifying these urban heat island-related externalities, comparisons among these three roofing strategies are limited. To date there have been a number of published case studies that compare green roofs to black roofs [9][10][11][12][13] and white roofs to black roofs [14][15][16][17]. However, we could not find a comprehensive comparison of green and white roofs.…”
Section: Sproul Et Al (Version Dated 11/01/2013)mentioning
confidence: 95%
“…The purely economic 50-year net savings of $25/m 2 ($2.40/ft 2 ) in favor of white roofs, though only $1/m 2 -year when annualized, is likely to underestimate of the true societal advantages of white roofs-namely, dark roofs pose a public health threat by exacerbating urban heat islands. We 16 See the Global Cool Cities Alliance's Cool Roofs and Pavements Toolkit (http://coolrooftoolkit.org) for a complete list of U.S. cool roof building codes and standards. 17 These net primary energy and cost savings differ from, but are based on, those reported in Table 1 …”
Section: Choosing a Roof Colormentioning
confidence: 99%
“…Sacramento, CA; Salt Lake City, UT; Chicago, IL; Houston, TX), Konopacki and Akbari at LBNL identifi ed an average 3.94% savings on building cooling energy consumption by applying high-albedo roof material to offi ce buildings metropolitan-wide [33].…”
Section: In a 2002 Department Of Energy (Doe) Simulation Study Of Fi mentioning
confidence: 99%
“…It is a phenomenon that is significant in itself since it occurs in the layer of the atmosphere where almost all daily human activities take place. Research has shown that heat islands have considerable implications for air quality (Rosenfeld et al, 1998;Sarrat et al, 2006;Davies et al, 2007), energy demand for cooling purposes (Santamouris et al, 2001;Konopacki and Akbari, 2002), human health (Conti et al, 2005;Haines et al, 2006), and regional/local atmospheric circulations (Lin et al, 2008;Miao et al, 2009). Further, although the UHI in itself does not influence global temperatures (Houghton et al, 2001), it does have an effect on local temperatures used for assessing climate change (Van Wevenberg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%